Percutaneous drainage in treatment for spontaneous rectus abdominis hematoma due to rivaroxaban usage - Dogan, Nurullah; Dursun, Aydin (The European Research Journal, 2016)
Rivaroxaban is currently used to prevent stroke in patients with atrial fibrillation. Like all anticoagulants, rivaroxaban carries a risk of bleeding. There is a single reported case of rectus abdominis hematoma due to rivaroxaban use in the literature. We present an 82-year-old female patient presented to our outpatient clinic with sudden pain and swelling in the abdominal region. The patient had been treated with rivaroxaban for three months without warfarin. Computed tomography scanning showed a 25x10x15 cm long acute hematoma in the left rectus abdominis. Rivaroxaban was replaced with enoxaparin for thromboembolus prophylaxis. We performed percutaneous drainage in order to reduce pain and recovery time by decreasing the hematoma size. Catheter drainage was used in the third day to minimize rivaroxaban activity. We did not come across any literature date on percutaneous drainage treatment of spontaneous rectus abdominis hematoma. We report a case of hematoma of the rectus abdominis muscle that occurred following rivaroxaban use and was successfully treated with percutaneous drainage